Hybrid fiber-reinforced geopolymer composites with enhanced impact resistance for marine structures - Yun Xu; Yichen Zhou; Ke Zhuang; Haoliang Wu; Qian Zhang; Kai Zhou; Boyin Ding; Xiaohuan Meng; Ziqun Wang; Zhenqiu Hu; Jingming Cai (Case Studies in Construction Materials)
To address the growing demands for corrosion-resistant marine infrastructure in chloride-rich environments, the mechanical properties and damage mechanisms of engineered geopolymer composites (EGC) reinforced with polyvinyl alcohol (PVA) fiber blends and polyethylene (PE) fiber blends under low-velocity impact were investigated in this study. By preparing EGC specimens reinforced with PVA/PE fiber blends with different volume doping (0–2 %), uniaxial tensile, compressive and low-velocity impact experiments were carried out to analyze the effects of fiber blending ratios on the material properties. The results showed that the PVA fibers enhanced the interfacial bonding through hydroxyl bonding, which significantly increased the tensile and compressive strengths of the materials, while the PE fibers exhibited excellent crack control and energy dissipation ability under impact loading due to their high specific surface area and hydrophobicity. During pseudo-static loading, the crack control ability of PVA fiber specimens was better than that of PE fiber specimens; however, PE fiber specimens were able to form a more homogeneous microcrack network under low-velocity impact. The PE/PVA fiber hybrid system (EGC-0.5–1.5) has comprehensive advantages in tensile ductility (7.86 %) and tensile strength (3.85 MPa), making it suitable for high impact demand scenarios. The pure PVA fiber hybrid system (EGC-2–0) can control the tensile crack width to around 39 μ m, while reducing the cost by 14–39 % compared to the PE fiber system. It is suitable for engineering scenarios that require strict crack control and economic considerations.